1993
DOI: 10.21273/hortsci.28.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides for Container-grown Rain Forest Species

Abstract: Four granular formulations of preemergence herbicides-oxadiazon, oxadiazon in combination with simazine, dichlobenil, and oxyfluorfen + oryzalin-were evaluated for weed control and phytotoxic effects on 10 species of container-grown Australian rain forest plants. Herbicides were applied at half and at one and two times the manufacturer's recommended rate. Oxyfluorfen + oryzalin, oxadiazon, and oxadiazon + simazine controlled all weed species at half the recommended rates (1.0 + 0.5, 2.0, and 2.0 + 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Another possible contribution to this negative effect can be due to the possible phytotoxicity of the herbicide. Different studies have reported that herbicides different from the one used here can have negative effects on the cultivated plant when used at high doses [30]. However, in this study, oxadiazon had no negative effect on V. lucidum plant growth when the herbicide was applied in non-inoculated containers (NIS-H treatment, Fig.…”
Section: Resultscontrasting
confidence: 49%
“…Another possible contribution to this negative effect can be due to the possible phytotoxicity of the herbicide. Different studies have reported that herbicides different from the one used here can have negative effects on the cultivated plant when used at high doses [30]. However, in this study, oxadiazon had no negative effect on V. lucidum plant growth when the herbicide was applied in non-inoculated containers (NIS-H treatment, Fig.…”
Section: Resultscontrasting
confidence: 49%
“…However, in cold weather they can be phytotoxic, especially with repeated applications, if they are present in the irrigation water (when it is applied to the foliage with watering), and if the water is unevenly applied (Bhandary et al, 1997;Glaze et al, 1987). Certain plants are more sensitive to oxadiazon, including Proteaceae (Sharman, 1993), daylily (Hemerocallis sp. 'Aztec Gold') (Norcini and Aldrich, 1992), and ivy (Ilex ×attenuata and Ilex crenata Thunb) (Thetford and Gilliam, 1991).…”
Section: Methodsmentioning
confidence: 99%